ANALISIS KUALITAS AIR LIMBAH WUDHU DALAM SISTEM DAUR ULANG BERKELANJUTAN - Irwan, Andesta Granitio; Pratama, Yudistira Bagus; Okta, Evan Dwi (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2024)
Water is one of the important elements in supporting human life so that optimal use of water can have a big impact on life. Water-saving practices, especially during ablution, are often uncontrollable, resulting in water-wasting behavior. In addition, the acidic pH conditions in some of the water samples used are feared to have a long-term adverse impact on individual users. This research provides a solution in saving water with an ablution wastewater recycling system for reuse by utilizing Internet of Things (IoT)-based monitoring that can record water usage discharge using a flowmeter while connected to a smartphone. In the simulation, a prototype is used which is designed as a water recycling system that can be monitored with the addition of a filtration system to filter waste and improve water quality, namely Total Dissolved Solids (TDS), Dissolved Oxygen (DO), and pH. The results showed that in total 52 samples, the average water usage was 2.45 liters / person and 42.31% were in the wasteful category. Comparison of water quality before and after filtering has a significant increase with TDS values reaching 118%, DO 41% and pH 42.31%. This increase shows better water quality after filtering so that it can be reused and the recycling results in the system used have an efficiency of 44% based on the comparison of monitoring volume and actual volume of water.